A Novel Selective JAK2 Inhibitor Identified Using Pharmacological Interactions - Lin, Tony Eight; HuangFu, Wei-Chun; Chao, Min-Wu; Sung, Tzu-Ying; Chang, Chao-Di; Chen, Yi-Ying; Hsieh, Jui-Hua; Tu, Huang-Ju; Huang, Han-Li; Pan, Shiow-Lin; Hsu, Kai-Cheng (Frontiers in Pharmacology, 2018)
The JAK2/STAT signaling pathway mediates cytokine receptor signals that are involved in cell growth, survival and homeostasis. JAK2 is a member of the Janus kinase family and aberrant JAK2/STAT is involved with various diseases, making the pathway a therapeutic target. The similarity between the ATP binding site of protein kinases has made development of specific inhibitors difficult. Current JAK2 inhibitors are not selective and produce unwanted side effects. It is thought that increasing selectivity of kinase inhibitors may reduce the side effects seen with current treatment options. Thus, there is a great need for a selective JAK inhibitor. In this study, we identified a JAK2 specific inhibitor. We first identified key pharmacological interactions in the JAK2 binding site by analyzing known JAK2 inhibitors. Then, we performed structure-based virtual screening and filtered compounds based on their pharmacological interactions and identified compound NSC13626 as a potential JAK2 inhibitor. Results of enzymatic assays revealed that against a panel of kinases, compound NSC13626 is a JAK2 inhibitor and has high selectivity towards the JAK isozyme family. In particular, NSC13626 shows high selectivity towards JAK2 and JAK3. Our cellular assays revealed that compound NSC13626 inhibits colorectal cancer cell growth by downregulating phosphorylation of STAT3 and arresting the cell cycle in the S phase. Thus, we believe that compound NSC13626 has potential to be further optimized as a selective JAK2 drug.